Maximize the capacity obtained from the solar battery system using p&o algorithm of mppt technique - Nguyen, Trường Nhu; Nguyen, Ngọc Xuân Huy (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
In this paper, the P&O algorithm in the technique of controlling maximum power point trackers applied in inverters to obtain the maximum power generated from the solar system is presented. Solar panels have non-linear voltage and current characteristics that depend on temperature and irradiance reaching PV panels and PV arrays have a unique point of being able to generate power maximum at each time point. The characteristics of solar radiation reaching the photovoltaic system are not stable at sunny times of the day, it is often changed by other factors such as partial cloud cover, total cloud cover or intensity, radiation varies by hour, by day and by season. As a result, the conversion of photovoltaic energy into electricity of PV panels will be changed. The power generated by the PV system is unstable, leading to low conversion efficiency. The application of algorithms in MPPT control technique to find the point that can generate the maximum power at any time in order to maximize the power received from the solar system. This paper will present simulation results to prove the correctness of the proposed method.